Medical information processing and security : techniques and applications - Kumar, Amit Singh; Zhou, Huiyu (Healthcare technologies series ;, 2022)
Smart healthcare systems, made up of advanced wearable devices, internet of things (IoT) technologies and mobile internet connectivity, allow significant medical information to be easily and regularly transmitted over public networks. Personal patient information and clinical records are stored on hospitals and healthcare centres and can be accessed remotely by healthcare workers. Due to the widespread increase in the sheer volume of medical data being collected and created all the time, it has never been more important to ensure that such information is collected, stored and processed in a reliable and secure manner. This edited book covers the recent trends in the field of medical information processing, including prediction of complications using machine learning and trends in visualization and image analysis. Further chapters focus on information security and privacy solutions for smart healthcare applications, including encryption of medical information, privacy in smart IoT environments, medical image watermarking and secure communication systems. Medical Information Processing and Security: Techniques and applications can be used as a reference book for practicing engineers, researchers and scientists. It will also be useful for senior undergraduate and graduate students, and practitioners from government and industry as well as healthcare technology professionals working on state-of-the-art security solutions for smart healthcare applications.